The Application Of The Laplace Transform In The Heat Equation - Ana Uzla BatuBara (CV. AFDIFAL MAJU BERKAH, 2023)
The one dimensional of homogeneous heat equation is two ordinary partial differential equations which general form , so needs solution. The one dimensional of homogeneous heat equation the method is ever been solved by Fourier series and Fourier Integrals. The other method used to in solving one dimensional of homogeneous heat equation is Laplace Transform, which is used to transform into ordinary differential equation is one dimension for initial conditions . Inverse general solution that satisfies boundary conditions is found, for every t and initial conditions that have been transform is . From the result, it an obtain temperature on the poin x in the solid at time t.